Computer-assisted analysis of TEM diffraction contrast images of (In,Ga)N/GaN nanostructures - Manolaki, P.; Häusler, I.; Kirmse, H.; Mogilatenko, A.; Neumann, W.; Smałc-Koziorowska, J.; Skierbiszewski, C. (Physica status solidi. C, 2008)
III‐nitride semiconductor nanostructures are subject of intense studies with respect to their optoelectronic, structural and chemical properties. Important parameters for the wavelength of the emitted light are the chemical composition and the dimensionality of the nanostructures. Transmission electron microscopy is used to determine these characteristics at a nanometer scale. In this work, the information provided by diffraction contrast images of (In,Ga)N/GaN quantum wells (QWs) is studied. Experimental dark‐field images alternatively using the 0001 and the 0002 reflection show a different contrast regime. In order to understand the contrast, one has to calculate the intensity Ig of the individual diffracted beam g. The intensity of the 0002 beam is a function of the sum of the atomic scattering amplitudes of the group III and the group V element. Consequently, the 0002 reflection is strain sensitive. According to the kinematical theory the 0001 reflection is forbidden. However, it is excited in the experiment. Therefore, dynamical effects have to be taken into account. The corresponding intensity is calculated by the Howie‐Whelan equations. It turns out that the intensity of the 0001 beam strongly depends on the In content of (In,Ga)N. A good agreement of intensity profiles of 0001 dark‐field images compared to the theory is found. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)